Factors Associated with Gastritis Incidence Among Adolescents Attending the Clinic - Narmi, Narmi; Arfiki, Laode; Jasmin, Muh. (PT. Nursing Genius Care, 2025)
Background: Inflammation of the inner lining of the stomach, known as gastritis, is caused by lesions in the gastric mucosa and inflammation of the gastric epithelium. Recurrence of gastritis due to irregular eating habits, inadequate nutrition or food quality, consuming too much or too little food, or consuming foods that are difficult for the body to digest will worsen the condition. Prolonged stress can also lead to the development of gastritis because it reduces blood flow to the gastric mucosa, increases its permeability and affects psychological well-being. Purpose: The aim of this study was to determine the factors associated with the occurrence of gastritis in adolescent members at the Teratai Clinic, Sat Brimobda Sultra. Methods: This research design uses a quantitative Cross Sectional approach. The number of samples is 50 people who suffer. Data analysis method with chi square test. Results: This study shows a correlation between stress (p value = 0.007) and diet (p = 0.000) Conclusion: at the Teratai clinic Sat Brimobda Sultra, the incidence of gastritis in adolescents is correlated with both food and stress. It is anticipated that suggestions will include more information about stress and nutrition for nurses.